2001
DOI: 10.1108/10662240110695106
|View full text |Cite
|
Sign up to set email alerts
|

Web‐based teaching materials: a user’s profile

Abstract: 2015),"Towards an automatic user profiling system for online information sites: Identifying demographic determining factors", Online Information Review, Vol. 39 Iss 1 pp. 61-80 http://dx. Access to this document was granted through an Emerald subscription provided by emerald-srm:333301 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 15 publications
2
18
1
2
Order By: Relevance
“…Numerous studies have reported no significant relationship between student learning style and satisfaction with web-based instruction (Kearsley, 2000;Kim & Moore, 2005;Stokes, 2003). Other studies, however, have reported that students' learning behaviour and course completion are influenced by their styles (Karuppan, 2001;Sabry & Baldwin, 2003;Terrell, 2002;Terrell & Dringus, 1999). Bajraktarevic, Hall, and Fullick (2003) found that students demonstrated better task performance when online activities were matched to their…”
Section: Learning Style and Web-based Learningmentioning
confidence: 94%
“…Numerous studies have reported no significant relationship between student learning style and satisfaction with web-based instruction (Kearsley, 2000;Kim & Moore, 2005;Stokes, 2003). Other studies, however, have reported that students' learning behaviour and course completion are influenced by their styles (Karuppan, 2001;Sabry & Baldwin, 2003;Terrell, 2002;Terrell & Dringus, 1999). Bajraktarevic, Hall, and Fullick (2003) found that students demonstrated better task performance when online activities were matched to their…”
Section: Learning Style and Web-based Learningmentioning
confidence: 94%
“…LSs are identified as an important dimension of adaptivity [6]. Other dimensions which may be influenced by adaptivity are discipline variance, students' achievement levels computer usage [12], etc. Thus, it is relevant to explore not only the impact of learning styles on performance, but also examine their impact based on different disciplines, students' general competence, and computer usage.…”
Section: A Hypermedia and Adaptive Hypermediamentioning
confidence: 99%
“…The evidence about many students' tendency to adopt a non-active role when exploring hypertext (Hiltz, 1997), to read the material linearly or sequentially (Beasley and Smyth, 2004) and to not consult all the resources and tools available to them (Light et al, 1997;Karuppan, 2001), although they are sufficiently trained to study online (Rodríguez et al, 2006), it leads the research team to propose various design criteria to simplify the structure of the hypertext. This first type of criterion involves, on one hand, establishing some limits to the presence of internal links (those between different parts of the material).…”
Section: Criterion 1 Simplification Of Hypertext Structurementioning
confidence: 99%
“…Indeed, the literature provides ample evidence that such initiatives do not always work: students often end up feeling 'lost' among all the material available to them (Burbules and Callister, 1996), make only a linear reading of the most important aspects (Light et al, 1997;Karuppan, 2001), or end up printing the material on paper (Crook, 1997;Ward and Newlands, 1998) and doing the reading, reflection and work outside the environment specifically designed for them. Indeed, the literature provides ample evidence that such initiatives do not always work: students often end up feeling 'lost' among all the material available to them (Burbules and Callister, 1996), make only a linear reading of the most important aspects (Light et al, 1997;Karuppan, 2001), or end up printing the material on paper (Crook, 1997;Ward and Newlands, 1998) and doing the reading, reflection and work outside the environment specifically designed for them.…”
Section: Introductionmentioning
confidence: 99%